info2u - Norman, Nur Alia; Ramli, Aliya; Mohd Helmi, Mohd Firdaus (Universiti Teknologi MARA, Kedah, 2017)
The tremendous growth of information has become a serious challenges for many peoples today. Everyday there are new information has been created either printed or non-printed. The use of search engine become a norm for most of the peoples as we tend to type anything in the search box to find what we looking for. However, the challenges is more on choosing the right information that the user retrieved. Therefore, info2u has been develop as a stop center for using to learn on how to evaluate information that they found in the internet. info2u will assist the user to evaluate the information based on the criteria that have been outlined. It will be equip with the related image and video to give better understanding to the users. It is aim to help the users to find the right information at the right time and at the right place. info2u will become one stop center for library users and students to learn on how to evaluate information. It also will equip them with knowledge and skills to find information at the right time and a right place.